BMT, Peluang dan Tantangannya - Peni Nugraheni (Jurnal Aplikasi Bisnis, 2017)
Baitul Maal wat Tamwill (BMT) is syariah micro financing organization that has developed becoming more than 3000 units since it is declared in 1994. BMT have large contribution to develop economic condition by giving loan to mikro enterprise. BMT has some strengthness if compared with other financing organizations, but there are also many weaknesses that must be solved. This article try to describe the prospect of BMT by using SWOT analysis and give some solution alternatif to support the future of BMT.